Taste cells depend on axon proximity to generate presynaptic sites - Shannon M. Landon; Emily Holder; Amber Ng; Ryan Wood; Eduardo Gutierrez Kuri; Saima Humayun; Laura Bordallo Pinto; Lindsey J. Macpherson (PLoS ONE, 2025)
The turnover and re-establishment of peripheral taste synapses is vital to maintain connectivity between primary taste receptor cells and the gustatory neurons which relay taste information from the tongue to the brain. Despite the importance of neuron-taste cell reconnection, the mechanisms governing synapse assembly in the taste bud are largely unknown. To determine whether nerve fiber connectivity is an initiating factor for the recruitment of presynaptic machinery in taste receptor cells, we use the expression of CALHM1 and Bassoon to identify presynaptic sites in type II (sweet, umami, bitter) and type III (sour) taste receptor cells, respectively. Under homeostatic conditions, the vast majority (>90%) of presynaptic sites are directly adjacent to nerve fibers (contacted). In the days immediately following gustatory nerve transection and denervation of taste buds, Bassoon and CALHM1 puncta are markedly reduced. This suggests that nerve fiber innervation is crucial for the recruitment and maintenance of presynaptic sites. During nerve fiber regeneration into the taste bud, presynaptic sites begin to replenish but are not as frequently contacted by nerve fibers as intact controls (35–54% compared to >90%). This reveals that taste cells rely on gustatory fiber innervation to organize presynaptic sites. Additionally, our finding that presynaptic sites are not as frequently contacted by regenerating axons suggests a model whereby trophic factors secreted by gustatory nerve fibers prompt taste receptor cells to produce and/or aggregate presynaptic specializations at the cell membrane prior to contact. This, in turn, may guide neurons to form mature synapses. These findings provide new insights into the mechanisms driving synaptogenesis and synaptic plasticity within the rapidly changing taste bud environment.